2018
DOI: 10.3102/0002831218794892
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Want to Come Off as Pushing an Agenda”: How Contexts Shaped Teachers’ Pedagogy in the Days After the 2016 U.S. Presidential Election

Abstract: Guided by perspectives on the sociopolitical contexts of schooling, control of teachers’ curriculum and instruction, and teaching of elections, we use findings from a national questionnaire to explore the contexts that shaped teachers’ pedagogical decision making following the 2016 U.S. presidential election. Our findings reveal that classroom, school, district, state, and national contexts often manifested in pressure from colleagues, parents, the administration, the district, and the public. This pressure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…Finally, results from this study support prior research that World Language teachers may feel unprepared or unmotivated to take up issues of identity (Baggett, 2018) and prior research that teachers across content areas often endorse colorevasiveness (i.e., Annamma et al, 2017) and a 'neutral' stance regarding identity and sociopolitical issues perceived to be political or partisan (Dunn, Sondel, & Baggett, 2019), such as race and racism. Previous research suggests that teachers might rationalize decisions not to address identities and sociopolitical issues in their classrooms by leaning on perceptions about student development (i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, results from this study support prior research that World Language teachers may feel unprepared or unmotivated to take up issues of identity (Baggett, 2018) and prior research that teachers across content areas often endorse colorevasiveness (i.e., Annamma et al, 2017) and a 'neutral' stance regarding identity and sociopolitical issues perceived to be political or partisan (Dunn, Sondel, & Baggett, 2019), such as race and racism. Previous research suggests that teachers might rationalize decisions not to address identities and sociopolitical issues in their classrooms by leaning on perceptions about student development (i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Processing emotions through dialogue and/or other means of expression is crucial. Second, educators must move beyond neutrality, guilt, shame, and disregard when it comes to historic systemic racism (Dunn et al, 2019). To aid in our understanding of this mind-set, educators must rely on an array of resources.…”
Section: Discussionmentioning
confidence: 99%
“…In these times, we see multiple instances of the challenges present in dialogue across ideologies and beliefs (Dunn et al, 2019). If teachers can build community by helping students facilitate dialogue by first laying out one’s feelings in a safe environment, as well as by sensitively considering multiple perspectives, and fully CRT toward critical pedagogical praxis, then perhaps we would have a society that is better equipped to engage in controversy and opposing opinions, but more, as Jacques noted above, to become active citizens in our democracy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some teachers chose topics they considered controversial in order to invite impassioned debate, others avoided topics they deemed too emotionally sensitive for their students in order to maintain what they believed to be a safe classroom space. Research surrounding the 2016 presidential election found that some teachers responded to their Muslim and immigrant students’ fears of a Trump presidency by avoiding discussion of the election outcome altogether, and trying to remain neutral ( Dunn et al., 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%